Forage resources and their utilization by herded cattle: A comparison of a grazing reserve and a farming area in the sub-humid zone of Nigeria - Bayer, W.; Kaufmann, Ralph R. von; Suleiman, H. (International Livestock Centre for Africa, 1984)
Describes the forage resources and their utilization by pastoralists' cattle in two of ILCA's case study areas in the sub-humid zone of Nigeria. Examines effects on cattle productivity. Presents some characteristics of the two case study areas, contribution of different grazing resources to total annual grazing time, and herd activities. Discusses transhumant vs settled pastoralism, herding against farming, and ranching vs pastoralism.